Technologies of dynamic access and shared use of the radioelectric spectrum - Cruz, Gerardo Martínez (Law, State and Telecommunications Review, 2019)
Purpose ”“ The quest to reduce the digital divide and increasing the traffic capacity of mobile networks to meet the demand for future connectivity led the Federal Institute of Telecommunications (IFT), through the Directorate of Engineering and Technology. Methodology ”“ Analysis of the state of the art of the technologies of dynamic access and shared use of the radioelectric spectrum (TADUCE) in order to identify those that are susceptible to adoption in Mexico. The technologies analyzed in the research are those based on LTE (Long Term Evolution) that operate in frequency bands of free use, emerging technologies based on MIMO, Cognitive Radio (RC), Device-to-Device (D2D) and TV White Spaces (TVWS) communications. Findings ”“ The DIT establishes different recommendations that the IFT must consider in order for these technologies to be optimally implemented in the country.